Cysteine cathepsins as therapeutic targets in inflammatory diseases. (2nd June 2020) - Vizovišek, Matej; Vidak, Eva; Javoršek, Urban; Mikhaylov, Georgy; Bratovš, Andreja; Turk, Boris
ABSTRACT: Introduction : Cysteine cathepsins are involved in the development and progression of numerous inflammation-associated diseases such as cancer, arthritis, bone and immune disorders. Consequently, there is a drive to progress research efforts focused on cathepsin use in diagnostics and as therapeutic targets in disease. Areas covered : This review discusses the potential of cysteine cathepsins as therapeutic targets in inflammation-associated diseases and recent advances in preclinical and clinical research. We describe direct targeting of cathepsins for treatment purposes and their indirect use in diagnostics. Expert opinion : The targeting of cysteine cathepsins has not translated into the clinic; this failure is attributed to off- and on-target side effects and/or the lack of companion biomarkers. This field now embraces developments in diagnostic imaging, the activation of prodrugs and antibody-drug conjugates for targeted drug delivery. The future lies in improved molecular tools and therapeutic concepts that will find a wide spectrum of uses in diagnostic and therapeutic applications.